Newsmaking Criminology: Korban Kejahatan Susila dalam Berita Media Online - Husen Mony; Desi Wahyuni (Unitri Press, 2023)
In the perspective of newsmaking criminology, news about crime does not represent facts. Often, the media orchestrate the other side of the actual event to attract attention. The purpose of this study was to determine: 1) newsmaking criminology in the news of victims of sexual crimes; 2) a prominent dimension in the news. The method uses quantitative content analysis, with the national online media news population. The main concept is newsmaking criminology with 6 dimensions. The result is that these 6 dimensions appear in the news under study. The dimensions of identity and photo exploitation are raised through the loading of photos of the victims' families; the words used distort the meaning of the event and the behavior of the perpetrator; while victim blaming and news objectivity are present through shifting the focus of news to family issues; Stereotypes arise through information on the behavior of the victim that causes the perpetrator to commit his actions. The conclusion of this research is the most prominent dimension in reporting, from 828 news articles, which are published in 5 national online media, namely: 1) the use of words or phrases, as many as 59 findings; and 2) identification of 31 findings. Abstrak Dalam perspektif newsmaking criminology, berita tentang kejahatan tidak merepresentasikan fakta. Seringkali, media mengorkestrasi sisi lain dari peristiwa sebenarnya untuk menarik perhatian. Tujuan penelitian ini untuk mengetahui: 1) newsmaking criminology dalam berita korban kejahatan susila; 2) dimensi yang menonjol dalam berita tersebut. Metodenya menggunakan analisis isi kuantitatif, dengan populasi berita media online nasional. Konsep utamanya newsmaking criminoogy dengan 6 dimensi. Hasilnya adalah 6 dimensi tersebut muncul dalam berita yang diteliti. Dimensi identitas dan eksploitasi foto dimunculkan lewat pemuatan foto keluarga korban; kata-kata yang digunakan mendistorsi makna peristiwa dan perilaku pelaku; sedangkan victim blaming dan objektifitas berita hadir melalui penggeseran fokus berita ke isu-isu keluarga; stereotype muncul melalui informasi perilaku korban yang mengabitkan pelaku melakukan perbuatannya. Kesimpulan dari penelitian ini adalah dimensi yang paling menonjol dalam pemberitaan, dari 828 artikel berita, yang termuat pada pada 5 media online nasional, yaitu: 1) penggunaan kata atau frasa, sebanyak 59 temuan; dan 2) pencantuman identitas, sebanyak 31 temuan.